PENGARUH MOTIVASI KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI (Studi Pada Mahasiswa FEB Universitas Budi Luhur Yang Bekerja) - Kencana, Fachri; Hendrawan, Koen (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the influence of Work Motivation, Compensation, and Work Environment on Organizational Commitment among working students of the Faculty of Economics and Business at Budi Luhur University. This research employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method and involves 110 working students from the Faculty of Economics and Business at Budi Luhur University. Data were collected through a Likert scale (1–5) questionnaire and analyzed using SmartPLS version 4.0. The results indicate that Work Motivation, Compensation, and Work Environment have a positive and significant effect on Organizational Commitment, with the Work Environment being the most dominant factor (coefficient = 0.536; t = 9.915; p = 0.000). Overall, these three variables explain 70.6% of the variation in Organizational Commitment (R² = 0.706), while the remaining 29.4% is influenced by other factors not examined in this study. These findings suggest that organizations should enhance work motivation through reward programs, ensure fair and equitable compensation systems, and create a comfortable and supportive work environment to strengthen the commitment of working students to their organizations.